FACTORS AFFECTING THE INTERNAL AUDIT EFFECTIVENESS - Mustika, Adhista Cahya (JURNAL AKUNTANSI DAN AUDITING, 2015)
This study tests the factors that influence the internal audit effectiveness, including internal auditor competencies, internal auditor independence, auditee support to internal audit activity, and the internal and external auditor relationship. Using the internal auditor inspectorate in Java Province, Indonesia, we found that the internal audit effectiveness can be attained through increase internal audit competence, independence and strong relationship between internal and external auditor. However, this study found that auditee support has no effect on internal audit effectiveness.